Foreign tour operators and travel agents knowledge of a potential tourism destination - Mulec, Ivo (Managing global transitions, 2012)
Vojvodina is an autonomous region of Serbia, and has the potential to become a successful tourism destination. Twenty years of changes have elapsed since the disintegration of Yugoslavia, and destination planners in Vojvodina are now looking to accommodate visitors and generate service related jobs. The method for collecting data was through survey responses from those in the travel industry. The objective for conducting this research is to analyze the knowledge and awareness of the developing destination of Vojvodina. From here, it is possible to get a sense of the region's awareness, and role tour operators and travel agents act as opinion makers in promoting destinations to their clientele. Results suggest that Vojvodina is not known as a tourism destination among foreign travel experts; furthermore, this would suggest that their clientele base is not informed of this region of Serbia as a tourism destination. Although not known, this is better than having a negative image. With a non-image, tour operators and travel agents then have the ability to creatively market and promote an image that will generate further awareness of the Vojvodina region as an emerging tourism destination.
Keywords: destinacije; destination awareness; destination image; destination knowledge; imidž; prepoznavnost; tourism; turizem; Vojvodina; Vojvodina region